PENGARUH PENERAPAN PROJECT BASED LEARNING MELALUI GOOGLE CLASSROOM TERHADAP HASIL BELAJAR SISWA PADA MATERI LAJU REAKSI: PROJECT BASED LEARNING - Widia Qholby; Lazulva (UIR Press, 2020)
The application of 2013 curriculum which has not been implemented perfectly become a problem in the learning process. This research aimed at knowing the effect of implementing Project Based Learning model with Google Classroom media toward student learning achievement on Chemistry subject, especially Reaction Rate lesson. It was an quasi experiment research with posttest only control group design. The eleventh-grade students of MIA were the population of this research. Random sampling was used in this research, and it was obtained the eleventh-grade students of MIA 1 (experimental group) and MIA 2 (control group). Interview, test, observation, and documentation were the techniques of collecting the data. Analyzing the data was using Independent t-test. Based on the results of Independent t-test with α=0.05, it was obtained the cognitive score of sig. (2 tailed) 0.046 (H0 was rejected). It showed that Project Based Learning model with Google Classroom media facilitated better learning achievement than the model without the use of Google Classroom media.